In the moonlight mist : a Korean tale - San Souci, Daniel; Neilan, Eujin Kim (Honesdale, Pa. : Boyds Mills Press, 1999)
A good-hearted woodcutter finds a heavenly wife in this retelling of a Korean folk tale.
Keywords: Folklore -- Korea